PENGEMBANGAN MODEL PEMBERDAYAAN KARANG TARUNA TERPADU DI DAERAH ISTIMEWA YOGYAKARTA - Elly Kumari Tjahya Putri (Politeknik Kesejahteraan Sosial Bandung, 2013)
Abstract Youth has opportunity to participate actively in social welfare to tackling social problems in their environment through Karang Taruna (a kind of social organization of youth). Therefore, it is important to empower Karang Taruna so as to promote youth involvement in social welfare. This study using action research metho to find an effectively model to be more empower in the social welfare participation. The study results showed that the Integrated Youth empowerment model was effectively improve the cadre in managerial aspects, succession planning, and professionality in social welfare, as well as in increasing active involvement of community leaders in youth coaching. This study recommend the need for: (1) development of youth recreational activities appropriate to the age level, (2) intensive assistance from the district/city Social Welfare Office, (3) development of networks among youth with stakeholder agencies such as; Local Manpower Office, Local Commerce Office, and also Social Welfare Office, and (4) development of cooperation network within the scheme of (Corporate Social Responsibility. Keywords : youth empowerment, youth organization, social welfare Abstrak Remaja mempunyai kesempatan untuk berperan aktif dalam usaha kesejahteraan sosial untuk menanggulangi masalah sosial di lingkungannya melalui wadah Karang Taruna. Oleh sebab itu, Karang Taruna perlu diberdayakan agar mampu mendorong keterlibatan aktif remaja dalam usaha kesejahteraan sosial. Kajian ini menggunakan penelitian tindakan untuk menemukan metode pemberdayaan Karang Taruna yang efektif, Hasil penelitian menunjukkan bahwa Model pemberdayaan Karang Taruna terpadu mampu meningkatkan kemampuan kader pengurus Karang Taruna dari aspek manajerial, kaderisasi, serta profesionalitas dalam usaha kesejahteraan sosial, serta meningkatkan keterlibatan aktif tokoh masyarakat dalam pembinaan Karang Taruna. Dari hasil penelitian direkomendasikan perlunya: (1) pengembangan kegiatan rekreatif remaja sesuai dengan usianya, (2) pembinaan intensif oleh dinas sosial Kabupaten/Kota, (3) pengembangan jaringan kerja antar Karang Taruna, maupun dengan instansi terkait sebagai pembina (Dinas Tenaga Kerja, Perdagangan, sosial), dan (4) pengembangan jejaring kerja sama dengan skema CSR (Corporate Social Responsibility). Kata kunci: pemberdayaan remaja, karang taruna, kesejahteraan sosial